The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/polym14112243
|View full text |Cite
|
Sign up to set email alerts
|

A New Process of Preparing Rice Straw-Reinforced LLDPE Composite

Abstract: To reduce the pollution resulting from discarding waste plastic film and burning straw, a new method of preparing straw-reinforced LLDPE composites was developed to utilize these wastes. The straws were first laid parallel on an LLDPE film and then rolled up. The rolls containing long straws were laid into a mat and then hot-pressed into a long straw composite board (the mass of straw accounted for 60%). Slope-cutting the straw, grinding the straw, and twisting the roll were designed to improve the physical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…The decreasing of Tm 2 for LB‐10 composite film than pure LLDPE film may be happened for the early denaturation of collagen contents in LB 4 . Similar thermal behavior was observed for LLDPE based composite films in previous studies 20,21,43 . The DSC thermo‐grams showed that the melting point of fabricated composite films were better than pure LLDPE film.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The decreasing of Tm 2 for LB‐10 composite film than pure LLDPE film may be happened for the early denaturation of collagen contents in LB 4 . Similar thermal behavior was observed for LLDPE based composite films in previous studies 20,21,43 . The DSC thermo‐grams showed that the melting point of fabricated composite films were better than pure LLDPE film.…”
Section: Resultssupporting
confidence: 72%
“…The complete degradation temperature of those composite films were slight lower than pure LLDPE film. The decrease of complete degradation temperature of composite films was due to the addition of leather fiber, which might be completely degraded earlier than pure LLDPE 9,21,43 . Thermal properties analysis are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RS can be utilized diversely, for example, in animal feed, as a substrate for mushroom cultivation, as biomass, and for biochar production [ 6 ]. Additionally, it can be mixed with polymers to produce various products such as automotive components, artificial wood, and composite films [ 7 , 8 , 9 , 10 , 11 , 12 ]. RS can help increase the strength of the polymer when it has an appropriate particle size and is mixed in proportion [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A new process for the manufacture of straw-reinforcing thermoplastic composites study revealed that the structure improved the LLDPE matrix' s reinforcement. The Dynamic mechanical analysis, differential scanning calorimetry, and thermogravimetric analysis have indicated that the composites manufactured by the wrap and twist method reduced viscous deformation and increased rigidity (Xu et al 2022) .…”
Section: Introductionmentioning
confidence: 99%